The determination of a complex criterion for assessing the performance of traction rolling stocks - Vaičiūnas, Gediminas; Lingaitis, Leonas P.; Bureika, Gintautas (Transport, 2004)
For assessing the quality of rolling stocks, the research was made into the operational expenses aimed to derive their relation with the time of rolling stock operation which could be used as a basis of the above generalized complex criterion. In this way a dimensionless composite index with the value not exceeding one was obtained for assessing the locomotive performance. If this index is more than one, the rolling stock should be written off as inefficient and obsolete equipment. First Published Online: 27 Oct 2010